KONSTRUKSI KREATIF PEMEROLEHAN KOMPETENSI PRAGMATIK ANAK USIA PRASEKOLAH - Werdiningsih, Dyah (Diksi, 2015)
This article is about a research conducted with the objective of studying the process of creative construction, which consists of a process of hypothesis formulation and that of hypothesis testing, in Javanese-Indonesian bilingual preschool children’s acquisition of pragmatic competence in using Indonesian. Employing a longitudinal research design, the research used subjects of different ages: preschool children 2, 3, 4, and 5 years of age. The data were compiled by means of observations together with data recording by using electronic recording equipment and field-note data cards. The data were analyzed by using a technique of performance analysis. On the basis of the data analysis, it has been found that the creative construction in the acquisition of pragmatic competence has been seen in preschool-age children’s use of learning strategies, which consist of two types: cognitive and social strategies. Keywords: creative construction, pragmatic competence, child learners